1996
DOI: 10.1096/fasebj.10.12.8903512
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of crescentic glomerulonephritis by antibodies to monocyte chemotactic and activating factor (MCAF/MCP‐1)

Abstract: We investigated the pathophysiological role of a potent macrophage (M(phi)) chemotactic cytokine (chemokine), monocyte chemotactic and activating factor/monocyte chemoattractant protein-1 (MCAF/MCP-1), in an animal model of crescentic glomerulonephritis. Administration of a small dose of nephrotoxic sera induced severe proliferative and necrotizing glomerulonephritis, with crescentic formation in the early phase and glomerulosclerosis in the later phase, in Wistar-Kyoto rats. MCAF/MCP-1 protein was detected im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 9 publications
5
135
1
Order By: Relevance
“…Accordingly, in anti-GBM GN in WKY rats, neutralization of MCP-1 reduced glomerulosclerosis and improved renal function in the later phase of the disease. 37 In a similar model of GN in mice, neutralization of antibodies to MCP-1 resulted in a decrease in the deposition of collagen. 12 Nonetheless, Fujinaka et al 13 found a significant suppression of glomerular infiltration and proteinuria by blocking MCP-1 at the early phase of the disease but not at day 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in anti-GBM GN in WKY rats, neutralization of MCP-1 reduced glomerulosclerosis and improved renal function in the later phase of the disease. 37 In a similar model of GN in mice, neutralization of antibodies to MCP-1 resulted in a decrease in the deposition of collagen. 12 Nonetheless, Fujinaka et al 13 found a significant suppression of glomerular infiltration and proteinuria by blocking MCP-1 at the early phase of the disease but not at day 8.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In this model of GN, enhanced gene expression of chemokines has been demonstrated; however, most of the studies have focused on the acute phase of the disease. 13,37 Furthermore, studies with neutralizing antibodies and blocking reagents targeted acute glomerular injury and were used at day l, or at the same time as anti-GBM Ab administration, before the development of the disease.…”
mentioning
confidence: 99%
“…Chemokine blockade with specific Abs or chemokine antagonists has been shown to reduce monocyte influx and proteinuria in some of these models (7,10,11). Therefore, chemokine antagonism is thought to be a promising therapeutic approach for proliferative GN as well as for many other inflammatory diseases (12)(13)(14)(15)(16).…”
Section: P Roliferative Immune Complex Glomerulonephritis (Gn)mentioning
confidence: 99%
“…Antibody neutralization of MCP-1 has been shown to improve glomerulonephritis in nephritic rats [10]. Chemokines modified to behave as antagonists have been shown to be effective against arthritis in a murine model and asthma in a guinea pig model [11,12].…”
Section: Introductionmentioning
confidence: 99%